If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2 + 9n = 4n + 7 Reorder the terms: 2 + 9n = 7 + 4n Solving 2 + 9n = 7 + 4n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-4n' to each side of the equation. 2 + 9n + -4n = 7 + 4n + -4n Combine like terms: 9n + -4n = 5n 2 + 5n = 7 + 4n + -4n Combine like terms: 4n + -4n = 0 2 + 5n = 7 + 0 2 + 5n = 7 Add '-2' to each side of the equation. 2 + -2 + 5n = 7 + -2 Combine like terms: 2 + -2 = 0 0 + 5n = 7 + -2 5n = 7 + -2 Combine like terms: 7 + -2 = 5 5n = 5 Divide each side by '5'. n = 1 Simplifying n = 1
| -6x+2(x+8)=-24 | | 6(z-2)+5z-2= | | 5(x+4)=-2x-8 | | 8y+3(y-5)=6(y+1)-2 | | 3(c-5)+5=2+c-12 | | 3(1-10x)= | | -8(2-7p)=-16-8p | | 90-9x=-70-x | | 6v-32=2(v-8) | | x+x-3002=7878 | | x-2+9k+3= | | (Y+8)(y+3)=0 | | X^4-3x^2-6=0 | | 145=216-u | | 8-3h-6= | | 3m+1-m=-7+m-1+1 | | -10k=250 | | -3x-18=7(x+6) | | -8k+9k= | | 85=7x-5(4x-4) | | y=16x+260 | | -3x+12=-3(2x+2) | | -5x+7(x-3)=8x-9 | | 2x+-7=66 | | -7(3x-4)+7=-21x+35 | | -47=x-67 | | 3+6x=54 | | -x^2-9n-18=0 | | -3x+12=-3(2y+2) | | -14x-8=-7x-12 | | 7x+5(-2x+3)=-3 | | -2(5p-1)-5p=-40-8p |